Pemberdayaan Hukum Perempuan dalam Pencegahan dan Penanggulangan KDRT di Desa Betiting, Kecamatan Cerme, Kabupaten Gresik - Noer, Zakiah; Puspitasari, Dara; Setjoatdmadja, Sylvia; Ayudyanti, Ika; Kurniawan, Rizki (Jurnal Abdimas Multidisiplin, 2025)
Domestic violence remains a significant social phenomenon in Indonesia, especially experienced by women. The lack of legal knowledge and access to protection institutions are the main obstacles for women to protect themselves legally. This service aims to empower women through legal counseling about their rights and the available protection mechanisms. The implementation methods include direct counseling, interactive discussions, and the distribution of educational media to women in Betiting Village, Cerme District, Gresik Regency. The results show that legal empowerment of women through increased access to information, legal assistance, and strengthening social protection is very necessary to prevent and reduce cases of domestic violence while enhancing participants’ understanding of Law Number 23 of 2004 concerning the Elimination of Domestic Violence and the procedures for reporting domestic violence. This activity is expected to be a stepping stone in building.